A randomized comparison between misoprostol and dinoprostone for cervical ripening and labor induction in patients with unfavorable cervices - D’souza, Aparajita Sophia; Samuel, Clarence J.; Katumalla, Francis Sridhar; Gupta, Garima; Goyal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The induction of labor remains as one of the major challenges in obstetrics even in this modern era. The ideal priming agent is one that causes cervical change that is most similar to that seen in natural ripening process. This study was aimed to evaluate the safety and efficacy of intravaginal Misoprostol and compare its effects with intracervical dinoprostone gel for cervical ripening and labor induction in patients with unfavourable uterine cervices. Methods: This was a one-year prospective study conducted in the department of Obstetrics and Gynecology of a 800 bedded premier teaching hospital in Ludhiana. The study population consisted of all pregnant women admitted to the labor ward beyond 37 weeks of gestation and requiring induction of labor for various medical and obstetrical indications. Frequencies, proportions, mean and standard deviation were done while chi square and t-test were used for determination of significance. Results: A total of 153 mothers fulfilled the criteria to be included in the study of which 81 mothers were induced by misoprostol and 72 mothers by dinoprostone gel respectively. There was no statistical difference in the maternal age, parity and gestation at the onset of study in the two groups. The ANC complications were also statistically similar. There was no significant difference in the mean initial Bishop Score in the two groups. 3.42 in the Misoprostol group and 3.56 in the Dinoprostone group. The mean Bishop Score after 8 hour of the first dose was 7.86 in the Misoprostol group and 6.88 in the Dinoprostone group. The mean time taken from the induction to the onset of labor was 5.57 hours in the misoprostol group and 8.04 hours in the dinoprostone group. There were no cases of tachysystole or hyperstimulation in both the groups. Conclusions: Misoprostol is a more efficacious cervical ripening and labor inducing agent compared to dinoprostone gel and can be used safely in the North Indian setting.